Metaphor-based algebra animation - Bos, Rogier; Renkema, Winand (Aarhus University, 2022)
We investigated whether dynamical animations with visualizations based on metaphorical linking are more effective for grasping algebraic manipulations than static animations. The question is whether and how ideas from conceptual metaphor theory, in particular, embodied cognition, can be drawn to positively contribute to the design of effective animations for visualizing algebraic manipulations. In classroom tests, grade-7 students watched an animated video on algebraic manipulation, either with dynamic visualization, a visualized person dynamically performing the manipulations, or a more static video not based on those ideas. For higher-level students with some pre-knowledge of algebra, we found a small positive effect for dynamic and dynamic embodied videos. For lower-level students with no pre-knowledge of algebra, the embodied animation turned out to be adverse effective.
Keywords: Dynamic visualization; embodied simulation; object collection metaphor